Níveis críticos de fósforo no solo e nas folhas para a implantação de Eucalyptus grandis Hill ex Maiden, em quatro tipos de solos - Ismael, João José [UNESP]; Valeri, Sérgio Valiengo [UNESP]; Corradini, Lenine; Alvarenga, Sílvio Fernandes; Do Valle, Celina Ferraz; Ferreira, Manoel Evaristo [UNESP]; Banzatto, David Ariovaldo [UNESP] (My University, 1998)
Eucalyptus grandis were planted in a dark red latosoil (LEa) and in three quartzose sand soils (AQ 1, AQ 2, AQ 3) on April 12-16, 1996 after the phosphate fertilizer application of 0, 150, 300, 450 and 600 kg ha -1 P 2O 5 used in a triple superphosphate form. The climate is Cwa according to classification of Köppen. Before the application of the treatments, at the soil depth of 0 to 20 cm, the clay text was of 11% in the AQ 1, 9% in the AQ 2, 14% in the AQ 3 and 40% in the LEa, the soils AQ 1 and AQ 2 presented 2 mg dm -3 of P and the soils AQ 3 and LEa 5 mg dm -3 of P. The experimental design was a randomized block with five replications. Were estimated in the leaves and in the soil the critical levels of phosphorus in function of 90% of the maximum plant height and diameter attained by the plants six months after planting. Were evaluated the characteristics: plant height, stem diameter, phosphorus content in the leaves and in the soil recovered by the Melich-1 extractor and anion-exchange resin. Based on the results for the latosoil was obtained a P critical level for the plant height of 8 mg dm -3 related to the Melich-1 extractor and 13 mg dm -3 for the ion-exchange resin and for the diameter were 6 and 11 mg dm -3, respectively. In the leaves the critical level of phosphorus were 1.4 and 1.4 g kg -1 in function of height and diameter, respectively. In the sand soil it was not possible to esteem the critical levels of phosphorus in the soil and in the leaves, because there was a growing lineal relationship among the data of height of the plant, diameter of the stem and the concentration of phosphorus in the leaves with the elevation of the applied doses of phosphorus.
Phosphorus critical levels on soil and leaves for the implantation of Eucalyptus grandis Hill ex Maiden, in four types of soils
Keywords: Critical level; Eucalyptus; Growth; Leaves; Phosphorus; Soil